Food–drug interactions involving multiple mechanisms: A case study with effect of Capsaicin on the pharmacokinetics of Irinotecan and its main metabolites in rat. (January 2018) - Wang, Nanxi; Zhu, Chaoran; Zhang, Xinlin; Zhai, Xuejia; Lu, Yongning
Highlights: The pharmacokinetics changes of Irinotecan and its main metabolites were investigated. Capsaicin increased the systemic exposure of SN-38 to a significant extent in rat. Capsaicin caused significant plasma protein binding displacement of SN-38. Multiple interaction mechanisms were explored in vitro, in situ and in animals. Abstract: Capsaicin (CAP), the main ingredient of chili peppers, displays potent anti-tumor activity in several human cancers. Irinotecan, an anticancer agent with narrow therapeutic index, is subjected to disposition by several enzymes or transporters modulated by CAP. This study systematically investigated the CAP–drug interactions in vitro, in situ and in animals. Results indicated that after 7 days of 3 mg/kg CAP treatment, the AUC0-∞ of SN-38 was significantly increased to 1.48-fold compared to the vehicle treated rats. Meanwhile, it caused a significant plasma protein binding displacement of SN-38, lowered the liver to plasma concentration ratio and slight reduction of biliary excretion after CAP treatment. These results demonstrated that ingestion of CAP would increase the systemic exposure and toxicity of SN-38 to a significant extent in rats by affecting multiple enzymes and transporters at various stages.